2018
DOI: 10.1108/ijqrm-10-2016-0174
|View full text |Cite
|
Sign up to set email alerts
|

Mahalanobis-Taguchi system: state of the art

Abstract: Purpose The purpose of this paper is to show a bibliographical review of the applications of the MTS throughout the time and the different fields. Design/methodology/approach The Mahalanobis-Taguchi system (MTS) is an analytical method used for the diagnosis and/or pattern recognition of multivariate data for quantitative decision making. Findings Its scope is very broad, ranging from engineering, medicine, education, and manufacturing, among others. This work presents a classification of the literature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The Taguchi method is a well-celebrated technique that provides a structured and efficient methodology to streamline a process [25]. Significance of the application of Taguchi methods and its variants in different industrial applications is evident from the works of Mota-Gutiérrez et al [26], Jeyapaul et al [27], Beyer and Sendhoff [28], and Bendell et al [29]. Among others, Taguchi's approach was considered by the researchers to address process improvement in food [30][31][32], healthcare [33], electronics [34], and manufacturing [35,36] industries.…”
Section: Methodsmentioning
confidence: 99%
“…The Taguchi method is a well-celebrated technique that provides a structured and efficient methodology to streamline a process [25]. Significance of the application of Taguchi methods and its variants in different industrial applications is evident from the works of Mota-Gutiérrez et al [26], Jeyapaul et al [27], Beyer and Sendhoff [28], and Bendell et al [29]. Among others, Taguchi's approach was considered by the researchers to address process improvement in food [30][31][32], healthcare [33], electronics [34], and manufacturing [35,36] industries.…”
Section: Methodsmentioning
confidence: 99%
“…Due to minimal resources within the T-Method itself, the authors are relying on the progress of OA enhancement within the MT-Method for practical purposes. The most recent study conducted by Mota-Gutiérrez et al [16] which summarised the 18 year progress of the MTmethod in various industrial practices was found to be very helpful for this study since the area of dimensional reduction or variables optimization by several researchers are still being progressively enhanced till recently [7], [17][18]. This study provides a conceptual idea in applying the same concept to T-Method variable screening or optimization since very few studies have been conducted within that area.…”
Section: Related Studiesmentioning
confidence: 96%
“…The MD can be easily defined using the covariance matrix of learning samples and can be calculated faster and more easily than neural networks (NNs) and support vector machines (SVMs). The MD is still widely used for industrial and various other purposes (see a recent example [3]), and there have been cases in which the MD was said to have better recognition performance than NNs and SVMs if there are few learning samples [4][5][6][7]. Usually, the population covariance matrix Σ of the learning samples is unknown in advance.…”
Section: Introductionmentioning
confidence: 99%